Ideological Considerations in Official Dubbing in Iran (Altre Modernità, 2016)
In our globalizing world, audiovisual products are understandably considered tools that advertise their original language and culture. Most societies do not stand any interference from the outside, especially if it considerably opposes the socio-cultural norms. Translation is a practice of cross-cultural communication which most often complies with the socio-cultural guidelines and norms of the recipient society. However, translated products might face resistance as they can be regarded threatening and hostile by the ruling gatekeepers. Given the dramatic disparities between most languages and cultures, translators are not the only decision-makers and other agents have pivotal roles in the process of adapting the translated product to the dominant conventions and socio-cultural norms. This paper aims at shedding some light on the role which agents play in the process of dubbing, both for public access national television and for private home distribution. The study explores the effects of preliminary and operational norms, and cultural appropriation conducted at both textual and visual levels through a method including interview data and textual analysis. The results show that foreign movies dubbed into Persian in the religious context of the contemporary Iran are strictly controlled both before the process of dubbing and during and after the process of dubbing due to a number of socio-cultural, political, and ideological considerations.